2018
DOI: 10.1111/jhn.12607
|View full text |Cite
|
Sign up to set email alerts
|

Improving the nutritional intake of hospital patients: how far have we come? A re‐audit

Abstract: Background Malnutrition affects up to 33.6% of hospitalised patients, with consequences that are detrimental for both patients and healthcare providers. In 2015, an audit demonstrated inadequate nutritional provision and consumption by hospitalised patients, comprising a major risk factor for malnutrition. This re‐audit evaluates whether patients are meeting recommended energy and protein standards and estimated individual requirements, subsequent to food service improvements since 2015. Methods Patients (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Computed results based on the five studies that had previously estimated dietary provision of nutritional requirements found that 49% to 82.7% of patients had an energy gap and 37% to 74% of patients had a protein gap [13][14][15]17,19]. Our study revealed that intake-to-requirement gaps were higher in the older-adult population.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Computed results based on the five studies that had previously estimated dietary provision of nutritional requirements found that 49% to 82.7% of patients had an energy gap and 37% to 74% of patients had a protein gap [13][14][15]17,19]. Our study revealed that intake-to-requirement gaps were higher in the older-adult population.…”
Section: Discussionmentioning
confidence: 50%
“…Studies have measured food intakes in patients hospitalized in acute care wards, but rarely in rehabilitation units or NH and specifically in older adults [11,[13][14][15][16][17][18][19][20][21]. Most of these studies estimated food intake based on percentage intake of meal served (0%, 25%, 50%, 75%, or 100%) or on the larger threshold of meal served (<100%, <75% or ≤50%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of the dietary assessment method was completed by a range of individuals with researchers and dietitians being the most common professional groups (Figure 3) (12,21,23,25,26,37,39,40,43,46,50,52,56,62,63,68,69,73,74,76, 151,154,[156][157][158][159][160][161][163][164][165][166][167][168]170,171,175) . The majority of studies (n = 94, 60%) did not specify the type of oral diet that was quantified; where this was specified, regular texture (n = 31, 19%) was the most commonly quantified diet type (27,28,36,46,50,51,54,64,77,81,87,102,103,105,(107)(108)(109)116,128,130,132,139,142,150,159,160,165,172,174)<...…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Reasons for inadequate dietary intake vary greatly. Poor appetite, nil-by-mouth status, inadequate nutritional screening, missed meals for medical procedures, polypharmacy, limited dietary selection or nutritional inadequacy of hospital meals and food waste are all contributing factors 7. This project focuses on food waste.…”
Section: Introductionmentioning
confidence: 99%